An empire of print the New York publishing trade in the early American republic - Smith, Steven Carl 1981- (The Penn State series in the history of the book, 2017)
"Traces the evolution of New York's publishing trade from the end of the American Revolution to the Age of Jackson. Explores the gradual development of local, regional, and national distribution networks in the early republic"...Provided by publisher